Peran Orang Tua dalam Proses Pembelajaran Pendidikan Agama Islam di Masa Pandemi Covid-19 - Ach. Syaikhu (FALASIFA : Jurnal Studi Keislaman, 2021)
The Covid-19 pandemic has not ended until today. The spread of this virus give major impact, one of which is the necessity of a regional quarantine policy. In suppressing the number of the spread of covid-19, the Indonesian government has implemented a regional quarantine system (Lockdown) and PSBB (Large-Scale Social Restrictions) in line with the Decree of the Presidential Regulation of the Republic of Indonesia Number 99 of 2020 for the DKI Jakarta area and the Decree of the Minister of Health of Republic Indonesia Number HK.01.07/Menkes/248/2020 concerning the Determination of PSBB in Several Areas of West Java Province (Task Force for Handling COVID-19, 2020). This has an impact on various sectors of life, one of which is the education sector. The role of parents during the Pandemic has increased by supervising and accompanying children in the learning process. In this paper, the author wants to explain the role of parents in assisting the learning process of Islamic Religious Education in children during the Covid-19 pandemic.